Oral versus intra-vaginal imidazole and triazole anti-fungal treatment of uncomplicated Vulvovaginal Candidiasis - مقصود, ديما; سحر حسن; ثورة نعيسة (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Vulvovaginal Cadidiasis (VVC) is a lower genital tract disorder that occurs in 75% of women at least once in their life time , with 40—50% of women experiencing a second attack . Candida albicans is the species most often associated with VVC. Diagnosis is made by vaginal fluid specimen , microscopic examination and culture. There are variety of effective treatments that include topical or oral anti-fungal. A meta-analysis study showed that there was no significant difference regarding the effectiveness between oral and topical treatment of uncomplicated VVC . Although topical regimens are commonly, used oral treatment is preferred by patients because of the ease of administration and the reduced duration of use . Fluconazole is the most widely used Triazole antifungal agent for VVC . Objective: To compare the efficacy of oral Fluconazole and intra-vaginal clotrimazol in the treatment of uncomplicated Vulvovaginal Cadidiasis , determining the percentage of fungal infections from vaginal infections in general , study of the symptoms of fungal vaginitis , predisposing factors and its relationship to age , determining the relationship the degree of PH of vagina with fungal Vaginosis. Patients and methods: The study was conducted at the gynecologic outpatient clinics of Tishreen university hospital in lattakia in period between 2021-2022 . a convenient sample of 500 female patients with signs or symptoms of vaginitis had been picked up from the attendants of the previous setting according to the following criteria : age rand from 20-50 years, married , we took a wet swap from posterior vaginal fornix for microscopy , and dry swap for microbial cultures , then we tested vaginal PH .The patient with uncomplicated Vulvovaginal Cadidiasis had been divided randomly in two groups , the women of first group had been treated by single oral doses of Fluconazole 150 mg , while the second group had been treated by clotrimazol 200 mg as vaginal ovules for three days .Those women had to follow up one week , and one month after finishing their treatment and another swap had been taken from posterior vaginal fornix for microscopy. The clinical and mycological outcomes evaluated. RESULTS: The clinical cure rates in Fluconazole group and clotrimazol group at 7-14 follow up were 87,95 % and 83,13 % respectively (P-Value=0.6) . The clinical cure rates at day 30-35 in two groups were 85,5 and 79,51 respectively( P-Value=0.2) . The mycological cure rates of patients at day 7-14 follow up in the two groups were 81,92 and 69,87 respectively( P-Value=0.02). The mycological cure rates of patients at day 30-35 follow up in the two groups were 77,1 % and 62,6 % respectively( P-Value=0.01) . we found the fungus in 60% of patients by microscopy , 79% of patient had no risk factors , 65% of patient with Vulvovaginal Cadidiasis had vaginal PH = 4. CONCLUSION: Clinical cure (no symptoms ) was similar for oral and intra-vaginal anti-fungal medicines in both the short term( 7-14) day and a long term( 28-30) day , however oral antifungal medicines probably cleared yeast from the vagina (mycological cure ) better than intra vaginal ones in both short term , and long term . The number of unwanted effects reported were similar in the two group. Key words: Vulvovaginal Cadidiasis , Fluconazole , clotrimazol ,clinical cure , mycological cure.